Selling short as Ijarāh with Istiḥsān and its ethical implication - Sifat, Imtiaz Mohammad; Mohamad, Azhar (Brill, 2016)
For most scholars, the concept of selling short, where financial assets are sold without prior possession or ownership, transgresses Islamic principles. However, the Sharīʿah Advisory Council of the Securities Commission of Malaysia (SAC) went against the majority by permitting short selling in 2006. Conventional finance points out that short selling increases liquidity, facilitates price discovery, and enables informational efficiency. Muslim scholars are facing a dilemma: on the one hand, Sharīʿah principles dictate that Islamic capital market transactions and instruments should remain devoid of elements of ambiguity and prohibited characteristics, but on the other hand, the Sharīʿah also demands that the transactions be of social utility to the participating parties. It appears that the SAC allows regulated short selling on the basis of ijārah with istiḥsān. This article strives to highlight the jurisprudential issues regarding short selling and contribute to an Islamic angle on the ethical implications affecting this phenomenon.